2006
DOI: 10.1074/jbc.m604371200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p38α Mitogen-activated Protein Kinase in Lung Metastasis of Tumor Cells

Abstract: To study the role of p38 mitogen-activated protein kinase (p38) activity during the process of metastasis, p38␣؉/؊ mice were subjected to an in vivo metastasis assay. The number of lung colonies of tumor cells intravenously injected in p38␣ ؉/؊ mice was markedly decreased compared with that in wild-type (WT) mice. On the other hand, the time-dependent increase in tumor volume after subcutaneous tumor cells transplantation was comparable between WT and p38␣ mice. Platelets of p38␣؉/؊ mice were poorly bound to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…5). The activated c-Src-FAK complexes may then signal through the p38 MAPK/NF-B signaling pathways, leading to enhanced cell motility, invasion, and metastasis as shown in this and previous studies (4,9,31). The present findings suggest that MDA-9/syntenin and its interacting partners represent potential therapeutic targets to reduce cancer metastasis.…”
Section: Discussionsupporting
confidence: 81%
“…5). The activated c-Src-FAK complexes may then signal through the p38 MAPK/NF-B signaling pathways, leading to enhanced cell motility, invasion, and metastasis as shown in this and previous studies (4,9,31). The present findings suggest that MDA-9/syntenin and its interacting partners represent potential therapeutic targets to reduce cancer metastasis.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the p38␣ activity level may affect the commitment of ESCs to develop into different cell lineages. In another study, Matsuo et al (2006) reported that that the rate of metastasis of lung tumor cells injected into p38␣ ϩ/Ϫ mice was markedly decreased compared to that in wild-type mice. Further analysis revealed that the p38␣ ϩ/Ϫ mice have a lower expression of E-and P-selectin and a reduced interaction between tumor cells and ECs.…”
Section: Discussionmentioning
confidence: 98%
“…Of interest, in human umbilical vein endothelial cells (HUVECs) expression of dominant negative forms of p38alpha and p38gamma as well as its downstream kinase MK2, but not p38beta or p38delta, blocks VEGF (vascular endothelial growth factor) induced endothelial migration (117). However, a recent study showed a resistance of p38alpha +/− mice to experimental lung metastasis as compared to the normal mice following an intravenous injection of mouse melanoma F10 and Lewis lung carcinoma cells (118). These results indicate that p38alpha activity in tumor versus host may play an opposite role in regulating tumor invasion and metastasis.…”
Section: The Roles Of the P38 Pathway In Regulating Cell Invasion Andmentioning
confidence: 99%